The Role of Immunity in The Epidemiology of Adolescent Syphilis - Cityta Putri Kwarta; Nurul Fathiyyah; Ainun Ganisia; Rakhmalia Imeldawati (Biomedical Journal of Indonesia, 2026)
Introduction. Syphilis is a sexually transmitted infection (STI) caused by the bacterium Treponema pallidum and remains a global health problem with a significant increase in prevalence. Adolescents are vulnerable to syphilis because they lack sufficient sexual health information and services. This study aims to explore the role of cellular immune response in the pathogenesis of syphilis in adolescents and the factors that influence it. Methods. This research study adopted a systematic literature review methodology, sourcing data from PubMed, Scopus, Web of Science, and Google Scholar databases. Results. The results demonstrate a crucial involvement of macrophages, dendritic cells, and T lymphocytes in the cellular immune response against Treponema pallidum causes Syphilis. The immune response is principally influenced by variables such as age, nutritional status, and the presence of HIV infection. High infection rates are also attributable to factors such as risky sexual behaviour and socioeconomic conditions. Enhanced interventions, including comprehensive sexual health education and improved access to healthcare services, are crucial for mitigating the adverse effects of syphilis in adolescents. Conclusion. In conclusion, this research underscores the necessity of a deeper understanding of the immunopathogenic mechanisms of syphilis in adolescents to facilitate the development of more effective preventive, diagnostic, and therapeutic strategies.